2019
DOI: 10.1096/fj.201900483rr
|View full text |Cite
|
Sign up to set email alerts
|

α‐NETA induces pyroptosis of epithelial ovarian cancer cells through the GSDMD/caspase‐4 pathway

Abstract: Chemotherapy resistance is one of the most common causes of death among patients with ovarian cancer, and identifying novel antitumor agents is a priority. Here, we report that the novel molecule 2‐(anaphthoyl)ethyl‐trimethylammonium iodide (α‐NETA) induces epithelial ovarian cancer (EOC) cell pyroptosis through the gesdermin‐d (GSDMD)/caspase‐4 pathway. Furthermore, Cell Counting Kit‐8 fluorescence‐activated cell sorting analysis showed that α‐NETA treatment led to cell death in different ovarian cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 20 publications
2
68
0
Order By: Relevance
“…Pyroptotic cell death is associated with key morphological changes including the swelling of cells, osmotic lysis, and plasma membrane rupture [ 20 ]. Pyroptosis activation requires ASC dependent caspase-1, a key protein in the cleavage and secretion of active IL-1β and IL-18.…”
Section: Resultsmentioning
confidence: 99%
“…Pyroptotic cell death is associated with key morphological changes including the swelling of cells, osmotic lysis, and plasma membrane rupture [ 20 ]. Pyroptosis activation requires ASC dependent caspase-1, a key protein in the cleavage and secretion of active IL-1β and IL-18.…”
Section: Resultsmentioning
confidence: 99%
“…These results have also been confirmed in in vivo studies. Taken together, these findings suggest that induction of pyroptosis represents a new anticancer strategy for epithelial ovarian cancer therapy (62).…”
Section: Pyroptosis In Cancermentioning
confidence: 87%
“…As a critical form of cell death, pyroptosis has been reported to be involved in many physiological processes, such as regulation of tumor immune microenvironment [35], treatment of acute myeloid leukemia [36] and act as an innate immune effector against intracellular bacteria [37]. There are various researches showing an association between pyroptosis and tumor proliferation [38][39][40]. In this study, we found that tanshinone II A enhanced cell proliferation and inhibited apoptosis by up-regulating GSDMD expression on HeLa cells, especially at high concentrations.…”
Section: Discussionmentioning
confidence: 99%